IMPROVING SOFTWARE ENGINEERING PROGRAMME FROM STUDENTS' PERCEPTION - Bujang, Yanti Rosmunie; Wang, Hui Hui; Jali, Nurfauza; Mit, Edwin; Bujang Masli, Azman; Cheah, Wai Shiang; mat, Abdul Rahman; Tan, Ping Ping; Mohamad Hamdan, Norazian; Ahmad Khiri, Mohamad Johan; Wee, Bui Lin; Phang, Eaqerzilla; et al. (Centreo of Applied Learning and Multimedia, 2020)
Software Engineering is one the programme under Bachelor of Computer Science offered by Faculty of Computer Science and Information Technology, UNIMAS. The MQA has suggested the programme to change the degree to Bachelor of Software Engineering according to the Programme Standards by MQA.